Regulations In Liew Of Statutes In States Of Emergency In Indonesia - Ansori, Lutfil (Universitas Islam Indonesia, 2022)
The enactment of a Government Regulations in Lieu of Laws during states of emergency raises problems. This is evident so in the enactment of Government Regulation in Lieu of Law No. 1 of 2020 which was formed based on an emergency but used the framework of normal legal regime. Such has led to legal uncertainty and is hence vulnerable to abuse. This research was conducted to answer the problems regarding: the application of emergency laws in Indonesia and the government regulations in Lieu of Laws during states of emergency. This paper used normative legal research conducted by means of statutory, case study, and conceptual approaches. The study concludes that there have been some developments in the application of emergency law in Indonesia, since the status of the current public health emergency s is categorized as an emergency that must be responded to by legal regime in a state of emergency. From the aspect of legal regulation, it is apparent that there are various forms of emergency laws in Indonesia, and each of these legal forms has a different impact on the regulation and its legal binding power. However, the diverse arrangements of emergency laws are not supported by the standard concepts of the state of emergency and these arrangements tend to overlap which has caused ambiguity in the arrangement of emergency law in Indonesia. government regulations in lieu of laws that are stipulated the states of emergency bear the status of emergency regulations. Therefore, the issuance of a government regulations in lieu of Las in the state of emergency must comply with the legal principles of the state of emergency. On this basis, the issuance of government regulations in lieu of laws in the state of emergency must firmly determine the period of its validity as a way to ensure that the existence of the government regulations in lieu of laws does not create legal uncertainty.Keywords: government regulations in lieu of laws, state of emergency, emergency law. Peraturan Sebagai Pengganti Statuta Dalam Keadaan Darurat Di Indonesia Abstrak Pemberlakuan Peraturan Pemerintah Pengganti Undang-Undang pada saat keadaan darurat menimbulkan permasalahan. Hal ini terlihat dari lahirnya Peraturan Pemerintah Pengganti Undang-Undang Nomor 1 Tahun 2020 yang dibentuk berdasarkan keadaan darurat tetapi menggunakan kerangka rezim hukum yang normal. Hal tersebut telah menyebabkan ketidakpastian hukum dan karenanya rentan terhadap penyalahgunaan. Penelitian ini dilakukan untuk menjawab permasalahan mengenai: penerapan undang-undang darurat di Indonesia dan peraturan pemerintah pengganti undang-undang pada saat keadaan darurat. Tulisan ini menggunakan penelitian hukum normatif yang dilakukan melalui pendekatan perundang-undangan, studi kasus, dan konseptual. Kajian menyimpulkan bahwa telah terjadi beberapa perkembangan dalam penerapan hukum kedaruratan di Indonesia, karena status kedaruratan kesehatan masyarakat saat ini dikategorikan sebagai kedaruratan yang harus ditanggapi oleh rezim hukum dalam keadaan darurat. Dari aspek pengaturan hukum, terlihat bahwa ada berbagai bentuk hukum darurat di Indonesia, dan masing-masing bentuk hukum tersebut memiliki dampak yang berbeda terhadap pengaturan dan kekuatan mengikat hukumnya. Namun, pengaturan undang-undang darurat yang beragam tidak didukung oleh konsep standar keadaan darurat dan pengaturan ini cenderung tumpang tindih yang menyebabkan ambiguitas dalam pengaturan undang-undang darurat di Indonesia. peraturan pemerintah pengganti undang-undang yang mengatur keadaan darurat berstatus peraturan darurat. Oleh karena itu, penerbitan peraturan pemerintah pengganti Las dalam keadaan darurat harus sesuai dengan asas-asas hukum keadaan darurat. Atas dasar itu, penerbitan peraturan pemerintah pengganti undang-undang dalam keadaan darurat harus secara tegas menentukan masa berlakunya sebagai upaya untuk memastikan bahwa keberadaan peraturan pemerintah pengganti undang-undang tidak menimbulkan ketidakpastian hukum.Kata kunci: peraturan pemerintah pengganti undang-undang, keadaan darurat, hukum darurat.